Manajemen Pelatihan Pendidikan Bahasa di Pondok Pesantren Yanmu NW Praya Lombok Tengah - Suprapto; Ahyar; Hariri, Lalu Masrik (Institut Kariman Wirayudha Sumenep, 2024)
Yanmu NW Praya Islamic Boarding School is the first Islamic boarding school in West Nusa Tenggara that uses foreign languages ​​(English and Arabic) as the language of instruction/daily communication in the boarding school. The courage of the Islamic boarding school is certainly inseparable from the purpose of the Islamic boarding school itself in preparing their students to face an era that demands mastery of foreign languages. This study uses a qualitative research type with data collection carried out through several stages, such as observation, interviews and documentation. While the data analysis technique uses several stages, namely data reduction, presenting data and verification. The results of this study indicate that: (1) The language training design used by Yanmu NW Praya Islamic Boarding School is a modification of Dick & Carey. The training program includes English programs; a) 24hours-English, b) word deposit, c) story telling, d) virtual session. Arabic Language Program; a) muhadatsah b) Drill/ilqo’ mufrodat, c) Course, d) Masrohiyyah, e) art creation, d) ability, e) El-Syarif method course, f) Ayyami writing. (2) implementation of the language training program includes several stages such as the planning stage, organizing stage, actuating stage, controlling stage and evaluating stage.